Studi Korelasi antara Suhu Inkubator dan Intensitas Cahaya dengan Klasifikasi Suhu Tubuh pada Bayi Prematur - Dwiyanti Purbasari (Jurnal Kesehatan Amanah, 2025)
Premature neonate will experience rapid loss of body heat immediately after birth. Mortality of neonate is caused by changes in body temperature at birth, namely hypothermia.. The purpose of this study was to analyze the correlation of incubator temperature and light intensity with the classification of premature neonate body temperature. The research design used a correlational approach with a cross-sectional approach. The population of this study were premature neonates in the Perinatology ward and NICU of Waled Hospital, Cirebon Regency. The sample in this study were 32 neonates using purposive sampling. The instruments used were observation sheets, thermometers, luxmeters, thermohygrometers. Data analysis in this study used Chi square. The results showed that a correlation between incubator temperature and body temperature in premature neonates. (p value = 0.05; α = 0.05) and there is a correlation between light intensity with body temperature in premature neonates. (p value = 0.05; α = 0.05). Measuring the neonates body temperature and resetting the incubator temperature needs to be done periodically by health workers.